Isoperla riverae, a new stonefly species from the southeast Nearctic, with notes on sympatric species including the larval description of Isoperla lenati Szczytko & Kondratieff, 2015 (Plecoptera: Perlodidae) - Verdone, Chris J.; Beaty, Steven R.; Holland, Victor B.; Williams, Bronwyn W. (Zootaxa, 2023)
Isoperla riverae sp. n. is described from the southeastern USA. The new species is proposed based on details of the adult habitus, male aedeagus, vesicle, female subgenital plate, ovum chorion, and larval habitus. Supporting data includes color images, scanning electron micrographs, genetic analysis of DNA barcodes, and comparative morphology of cognate species. The larva of Isoperla lenati Szczytko & Kondratieff, 2015 is also described supported by color images.